The Impact of Jumps and Leverage in Forecasting Co-Volatility - Manabu Asai; Michael McAleer (Tinbergen Institute, 2015)
The paper investigates the impact of jumps in forecasting co-volatility, accommodating leverage effects. We modify the jump-robust two time scale covariance estimator of Boudt and Zhang (2013)such that the estimated matrix is positive definite. Using this approach we can disentangle the estimates of the integrated co-volatility matrix and jump variations from the quadratic covariation matrix. Empirical results for three stocks traded on the New York Stock Exchange indicate that the co-jumps of two assets have a significant impact on future co-volatility, but that the impact is negligible for forecasting weekly and monthly horizons.
Keywords: C32; C53; C58; G17; 330; Co-Volatility; Forecasting; Jump; Leverage Effects; Realized Covariance; Threshold